Design of Flight Closed Loop Simulation System Based on Runge-Kutta Algorithm. (November 2020) - He, Jinsong; Xiao, Jia; Li, Xiaojun
Abstract: To solve the problem that the function/performance of the module cannot be fully verified in the laboratory or in the field during the design stage of the airborne radar system, the paper proposes and designs an airborne flight closed-loop simulation system. The flight simulator, which is the core of the entire simulation system, uses the Runge-Kutta algorithm to solve the model and solve the 6-degree-of-freedom nonlinear model of the aircraft in real time, providing realistic aircraft movement data for the airborne radar system. The design builds a Matlab/Simulink simulation model and embeds it in simulation test software to run independently as a model component. The verification test of the closed-loop simulation system shows that the system can realize the real-time simulation of the entire flight environment and meet the design performance requirements.